2018
DOI: 10.1177/1479164117749382
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA nuclear paraspeckle assembly transcript 1 inhibits the apoptosis of retina Müller cells after diabetic retinopathy through regulating miR-497/brain-derived neurotrophic factor axis

Abstract: Our results suggested that under diabetic conditions, downregulated nuclear paraspeckle assembly transcript 1 decreased the expression of brain-derived neurotrophic factor through elevating miR-497, thereby promoting Müller cells apoptosis and aggravating diabetic retinopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 33 publications
0
16
0
1
Order By: Relevance
“…Reduced MALAT1 expression may impair neurotrophic factor-and stress-related gene expression by PI3K/Akt, MAPK, Ca2+/CaMK and cAMP/PKA pathways, all converging on the CREB family of leucine-zipper transcription factors [81]. NEAT1, slightly up-regulated during treatment period, could protect retinal Muller cells from apoptosis, also regulating splicing events involving genes related to cell cycle and cell death [82]. The opposite expression trends by MALAT1 and NEAT1 might represent a critical metabolic scenario with a final attempt by impaired cells to survive.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced MALAT1 expression may impair neurotrophic factor-and stress-related gene expression by PI3K/Akt, MAPK, Ca2+/CaMK and cAMP/PKA pathways, all converging on the CREB family of leucine-zipper transcription factors [81]. NEAT1, slightly up-regulated during treatment period, could protect retinal Muller cells from apoptosis, also regulating splicing events involving genes related to cell cycle and cell death [82]. The opposite expression trends by MALAT1 and NEAT1 might represent a critical metabolic scenario with a final attempt by impaired cells to survive.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that miR-497-5p can bind to the 3′ UTR binding site of BDNF ( Wang et al, 2017b ; Li, 2018 ). First, we used the luciferase assay system to determine the effect of miR-497-5p on BDNF translation.…”
Section: Resultsmentioning
confidence: 99%
“…However, another study found that MIAT has a highly homologous target sequence with miR-29b, which can negatively regulate the level of miR-29b and regulate Müller cell apoptosis in DR through the miR-29b/Sp1 axis ( 116 ). In addition to the damaging effect, lncRNAs also play a protective role in the nerve cells of DR. For example, upregulating the expression of NEAT1 in Müller cells in the HG state can downregulate miR-497 and increase the expression of BDNF, hindering the damaging effect of HG on Müller cells ( 114 ). Some lncRNAs can directly change the morphology of photoreceptors, such as MALAT1, which is upregulated through DR induction, which makes cones appear sparsely arranged and assumes the form of relatively short outer segments.…”
Section: Mirnas and Lncrnas Affect The Development Of Dr Through Retinal Nerve Cellsmentioning
confidence: 99%